Lipoxygenase (LOX) Pathway: A Promising Target to Combat Cancer - Vishnupriya, P.; Aparna, A.; Viswanadha, Vijaya P. (Current Pharmaceutical Design, 2021)
Leukotrienes are one of the major eicosanoid lipid mediators produced due to an oxidative transformation of arachidonic acid. Subsequently, they get converted into various cellular signaling hormones by a series of enzymes of myeloid origin to mediate or debilitate inflammation. Interestingly, the available literature demonstrates the pivotal role of eicosanoids in neurodegenerative, obesity, diabetes, cardiovascular diseases, and cancers as well. The aberrant metabolism of arachidonic acid by the LOX pathway is a common feature of epithelial-derived malignancies and suggests the contributory role of dietary fats in carcinogenesis. The enzymes and receptors of the LOX pathway play a significant role in cell proliferation, differentiation and regulation of apoptosis through multiple signaling pathways and have been reported to be involved in various cancers, including prostate, colon, lung and pancreatic cancers. So far, leukotriene receptor antagonists and 5-LOX inhibitors have reached up to the clinical trials for treating various diseases. Keeping its various roles in cancer, the review highlights the components of the leukotriene synthesizing machinery, emerging opportunities for pharmacological intervention, and the probability of considering lipoxygenases and leukotriene receptors as good candidates for clinical chemoprevention studies.
Keywords: arachidonic acid